(untitled) (Philological Studies, 2019)
The focus of sociolinguistic research has currently shifted from studying proper sociolinguistic variables to their evaluation and language attitudes. One of the evaluation parameters is regional speech marking which allows relating the speaker to a particular region. The report presents a study of evaluating Perm urban oral speech by speakers of the same regiolect. The object of the study is the dependence of the regional speech marking on the usage sphere. The results show that while evaluating oral speech of the media and everyday speech the listners rely on different perceptual attributes, i.e. speech evaluation depends not only on the proper linguistic characteristics, but also on its usage sphere.